Anti-Fungal Activity Test of Sengkuang (Dracontomelon dao) Leaf Ethanol Extract on The Growth of Candida albicans - Aima Insana (Baiman Bauntung Batuah Center, 2022)
Candida albicans is an important opportunistic fungal pathogen that is responsible for the majority of fungal infections in humans. In healthy individuals, Candida colonizes mainly on the mucosal surfaces of the oral cavity, digestive tract, skin and genitals. Dracontomelon dao or known as Sengkuang has been used as a traditional medicine for various diseases. Based on various studies, Dracontomelon dao extract is reported to exhibit antimicrobial properties. This study aimed to analyze the antifungal activity of the ethanol extract of sengkuang (Dracontomelon dao) leaves on the growth of Candida albicans. The study used 96% ethanol extract by macerating the simplicia leaves of Dracontomelon dao originating from South Kalimantan, Indonesia. The antifungal activity was tested by well diffusion method at various concentrations of the test extract (10%, 20%, 30%, 40% and 50%). The results showed that the average diameter of the inhibition zones at concentrations of 10%, 20%, 30%, 40% 50% were 19.2 mm, 21.8 mm, 23.2 mm, 24.8 mm, 27 mm, respectively. Based on the results of the study, it was found that the ethanolic extract of sengkuang (Dracontomelon dao) leaves had antifungal properties against the growth of Candida albicans with the most effective concentration at a concentration of 50% with an average zone diameter of 27 mm. The content of phytochemical compounds from sengkuang leaf extract (Dracontomelon dao) are flavonoids, alkaloids, saponins, tannins, and triterpenoids. This secondary metabolite is thought to be able to inhibit the growth of the fungus Candida albicans. The ethanol extract of sengkuang leaves (Dracontomelon dao) has been shown to have antifungal activity in vitro so that it has the potential to be developed as an antifungal agent and can be a new solution in handling cases of Candida albicans infection.